Plan estratégico de marketing para posicionar la empresa Ferri Aserrío Solano en el Cantón Zaruma, Provincia de El Oro, Periodo 2021-2022 - Torres González, Milena Maribe (2023)
The objective of this research is to develop a Strategic Marketing Plan to position the Ferri Aserrío Solano Company in the Zaruma Canton, El Oro Province, 2021-2022 Period. A situational diagnosis was made, investigating the external and internal environment. Consequently, for the development of the research, a descriptive qualitative approach and a non-experimental quantitative approach were used, using techniques and instruments of information collection such as direct observation, interview with the manager and the survey, which was applied to internal clients and 200 external clients using the non-probabilistic method for convenience, as a result of the external analysis corresponding to the PESTE analysis and Porter's five forces. The EFE matrix was made, where a weighting of 2.53 was obtained, which indicates that the company is slightly well in relation to the threats. In addition, the competitive profile matrix was developed where the company has a weighting of 3.09 with respect to its four main competitors. In the internal analysis, the EFI matrix was developed with a weighting of 2.58, highlighting the strengths against the weaknesses within the organization. Likewise, the BCG matrix, of Ansoff, and the Internal-external matrix were made with market penetration strategies. Finally, the high impact matrix was elaborated, which allowed the development of the proposal of the strategic marketing plan, in which six micro strategies corresponding to product, price, promotion, post-service sale, merchandising, and positioning were proposed, which make up the macro strategies on marketing mix, positioning and loyalty, which provide benefits as a whole to position the company commercially. Finally, the conclusions are presented; among the most relevant is the lack of advertising and promotion. The application of the strategies of the marketing plan is recommended to improve the shortcomings found in the company.